Wasavi + anti-jware detection system - Claudio, Benjamin Pio.; Lee, Marvin; Sibayan, Maybelle (2006)
WASAVi, is a Windows Application and Anti-Jware, is a Windows Mobile Application, developed at the University of the Philippines, Diliman for the purpose of detecting and removing malware in desktop systems and Pocket PC handhelds, respectively. Given that WASAVi was designed for desktop systems, Anti-Jware is redefined given the initial software design of WASAVi to better fit mobile devices. Anti-Jware uses the MD5 hashing algorithm for virus detection. Similar to both WASAVi and Anti-Jware are the filesystem scanning, running processes scanning, registry scanning and Pattern File updating capabilities. WASAVi and Anti-Jware is divided into modules designed for each capability. The File Scanning Module executes the filesystem scanning and deletes the files that matches with virus listings in the pattern file. The Running Processes Module executes the running processes scanning and terminates the running process related to any virus listed in the pattern file. The Registry Scanning Module executes the registry scanning and deletes registry values connected with a virus located in the virus list definitions. The Pattern File Update Module provides the mechanism in increasing the security provided by WASAVi and Anti-Jware with an uploaded pattern file.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Computer security; Computer viruses -- Prevention -- Software; Malware (Computer software) -- Prevention; WASAVi